Analysis of the similarities and differences between Auclandia and Vladimirae rhizomes by chemical profiling and chemometric analysis. (12th June 2020) - Chen, Ziqiang; Li, Qijuan; Yu, Ziwei; Yan, Xiaomin; Wang, Wenjun; Xie, Yu; Hu, Huiling; Wang, Zhanguo
Abstract: Ethnopharmacological relevance: Aucklandiae Radix (AR) and Vladimiriae Radix (VR), as traditional Chinese medicine, have been included in many editions of Chinese Pharmacopoeia with similar efficacy such as promoting qi and relieving pain, which are used to treat chest, hypochondriac, abdominal fullness and pain, diarrhea and tenesmus. In most conditions, VR is used to be a substitute of AR or a local habit. However, whether VR could substitute for AR to play a same role in the formulation and clinical applications needs further study. Aim of the study: In this study, similarities and differences between AR and VR would be assessed, and possible reasons that may influence the efficacy of the AR and VR would be explained from the perspective of chemical composition. Materials and methods: HPLC-PDA was used to obtain the data of 10 batches of AR and VR, and to establish chemical fingerprint and chemometric analysis. UPLC-ESI-Q-TOF-MS was used to identify the structure of chemical compounds which contributed to the differences between AR and VR. Results: The chemical fingerprint analysis results showed that 20 peaks in common for AR and 26 peaks in common for VR both presented a good similarity (>0.9), and 15 peaks in common for AR and VR also showed a good similarity (>0.9). Nevertheless, chemometric showed AR was distinct from VR and three chemical compounds, which leading to their differences, were identified by UPLC-ESI-Q-TOF-MS. The three chemical compounds were 3β-acetoxy-11β-guaia-4 (15), 10 (14)-diene-12, 6α-olide, 10α, 14-epoxy-11β-guaia-4 (15)-ene-12, 6α-olide and costunolide, respectively. Conclusion: In general, AR and VR were highly similar, but their differences were deserved to be paid attention to. This research could provide reference for quality control and set a foundation for clinical applications of AR and VR. Graphical abstract: Image 1 Highlights: Optimize chromatographic conditions while ensuring adequate information acquisition. Similarity analysis results support the theory that VR substitutes for AR, but differences between them should be noticed. Difference analysis found three compounds that affect the differences between AR and VR. Identify the structures of the three compounds, laying the foundation for later quality assurance and clinical usages.